(untitled) (Indian Journal of Animal Production and Management, 2016)
Somatic cell count (SCC) in milk has been shown to be an excellent marker for subclinical mastitis but very difficult to execute at farm level. Due to the damage to the udder tissue, concentrations of lactose decrease and concentrations of Na+ and Cl increases in milk which results in increase in electric conductivity. The present investigation was carried out to investigate the correlation of milk lactose and electric conductivity with somatic cell count and can be used as an indicator to detect subclinical mastitis (SCM) in Indigenous zebu Tharparkar cattle. Total 466 milk samples were screened for somatic cell count, 198 samples were positive for subclinical mastitis. All the samples were analyzed for electrical conductivity (EC) and milk lactose by deluxe electric conductivity meter manufactured by Systronics India limited, Ahamdabad and ultrasonic milk analyzer manufactured by Rajasthan Electronics & Instrument Limited (REIL), Jaipur respectively. The result demonstrated statistically significant (p<0.01) increase in electric conductivity and significant (p<0.01) decrease in milk lactose. From the results a conclusion can be made that electrical conductivity and milk lactose exhibits a high correlation with SCC scores and can be used as the tools to predict subclinical mastitis at farm level.